Aesthetics, romanticism(s), and poetic modernity - Falleiros, Flávia Nascimento (Lettres Françaises, 2016)
This paper aims to research the background of the notion according to which Baudelaire occupies the central place in poetic modernity. In order to do so, we propose to examine two important moments: Romanticism in its various manifestations and the establishment of Aesthetics as an autonomous subject.